Barrow Knowledge: Ritual Practices and Monumental Ideas - Holst, Mads; Krištufová, Tereza; Potrebica, Hrvoje (2008)
The session aims to explore ideas and knowledge expressed and transmitted in the architecture of barrows and in the associated burial events. There has for some years now been an increased focus on the detailed study of the history of individual monuments, stimulated by both changed theoretical emphasis and improved excavation methods. These studies have revealed complex and varied activity sequences and provided insights into ideas associated with the barrows. Thereby the significance of the monument and its accompanying activities in the development and dissemination of constructional and cosmological knowledge has been emphasized. At the same time, the changed focus and the disclosure of considerable variation in the histories of monuments represent a distinct contrast to the concept of the barrows as expressions of geographically widespread common ideas as in theories of Megalithic cultures and Kurgan-waves. It is the intention of this session to provide a basis for a general discussion of the character of the knowledge and ideas associated with barrows and the possibilities of approaching these aspects through the detailed studies of the monuments and their activity sequences. It is hoped that the session will stimulate a debate on - how knowledge and ideas were transmitted between monuments, - how the local uses and developments of ideas of the individual monuments relate to the barrow as a geographically and chronologically widespread phenomenon and - the validity of the concept of common ideas of the barrow.
Projekt MZOS
ENG